Some ornamental shrubs adapted to the climate of kansas - Adams, Carl D. (My University, 1895)
Introduction: When an eastern man passes through this state he is surprised at the rapid strides the country has made. He expected to see a broad trackless prairie dotted here and there with a sod-house or a hay-stack, but he finds instead a well cultivated prosperous farming community with good substantial farm houses and out buildings. These he notices as he passes along on the train, but when he stops to make closer observations he finds that many of the homes are unadorned by trees, shrubs, or climbing vines.
Citation: Adams, Carl D. Some ornamental shrubs adapted to the climate of kansas. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Farming; Trees; Shrubs; Climbing vines; Theses; Manuscripts (documents)